2013
DOI: 10.1002/rcs.1542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the initial surgical experience with robotic and laparoscopic myomectomy

Abstract: RM may have some additional advantages compared with LM in terms of bleeding and uterine suturing without compromising operation duration, at least when surgeons were at the beginning of their experience of endoscopic treatment of symptomatic uterine myomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 18 publications
2
33
1
Order By: Relevance
“…Another factor for the long mean operative time of this study is the number of removed myomas. In this study, the mean number of removed myomas for each case was 3.8 ± 3.5 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This is greater than the values in other studies (4,7,8,11,12).…”
Section: Discussionmentioning
confidence: 68%
“…Another factor for the long mean operative time of this study is the number of removed myomas. In this study, the mean number of removed myomas for each case was 3.8 ± 3.5 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This is greater than the values in other studies (4,7,8,11,12).…”
Section: Discussionmentioning
confidence: 68%
“…Appropriate surgical technique has been indicated to minimise the detrimental effect of surgery on the ovarian reserve [6,21]. In our opinion the development of new surgical approaches should always be compared to the conventional treatment [22]. Single-port access laparoscopy has been recently developed and many studies have evidenced its advantages and limits in gynaecological surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies including multiple centers and a higher number of patients are needed to confirm our results. Moreover, considering the results obtained in some studies which have demonstrated the differences between beginner and experienced surgeons in robotic surgery, such as the study by Pluchino et al [15], it could be interesting to evaluate in future studies differences between skilled and not surgeons in both laparoscopy and robotic approach.…”
Section: Commentmentioning
confidence: 98%